Exploring Phytochemical Compounds: A Computational Study for HIV-1 Reverse Transcriptase Inhibition - Bandi, Jyotsna; Chunduru, Madhan; Mangamuri, Satya Tulasi; Nelapati, Anand Kumar; Naravula, Jalaja; Mulpuru, Viswajit (Current Proteomics, 2024)
BackgroundHIV-1 is the most virulent type, causing most AIDS cases worldwide. Therapeutics like NRTIs and NNRTIs terminate replication by terminating polymerization reactions. Natural-based therapeutics are increasingly being used to reduce side effects and combat disease.MethodsThe study focuses on identifying phytochemical compounds that effectively inhibit the HIV-1 reverse transcriptase process using molecular docking and molecular dynamic simulations.ResultsMolecular docking results show anisomelolide has a significantly stronger binding affinity (-29.9992KJ/mol) compared to nevirapine (-13.34696 KJ/mol), forming more hydrogen bonds and hydrophobic interactions, indicating a more stable and specific binding. MD simulations further support these findings, with anisomelolide exhibiting lower RMSD and RMSF values, suggesting greater structural stability and lower flexibility. Interaction energy analysis reveals robust binding and stability for anisomelolide over time. Additionally, hydrogen bond analysis indicates more frequent and stronger interactions for anisomelolide.ConclusionThe phytochemical compound anisomelolide exhibits superior binding affinity, structural stability, and interaction dynamics, making it a promising candidate for drug development against HIV-1 RT.
Keywords: HIV